Postmodernisme en modernisme na 1945 : van het Atomium tot het Huis Van Roosmalen - Bekaert, Geert, 1928-2016; Braeken, Jo, 1957- (Tielt : Lannoo, 2008)
Oostende, Sint-Lambrechts-Woluwe, Grimbergen, Antwerpen, Kraaoinem, Moorsel, Ukkel, Evere, Nieuwpoort, Namen, Brussel, Luk, Oostende, Sint-Genesius-Rode, Buzenol, Herent, Antwerpen, Sint-Martens-Lennik, Morlanwelz, Sart-Tilman, Chevetogne, Oud-Turnhout, Westmalle, Angleur, Overijse, Mechelen? Battel, Sint-Lambrechts-Woluwe, Sint-Martens-Latem, Louvain-la-Neuve, Waasmunster, Overijse, Wasmes, 's-Gravenwezel
Keywords: Modernisme